Bioaccessibility of paralytic shellfish toxins in different cooked shellfish using the simulated digestive model. (1st October 2022) - Qiu, Jiangbing; Zhang, Lei; Cao, Yadong; Zhao, Peng; Zhang, Jingrui; Li, Aifeng
Graphical abstract: Highlights: The digestive enzymes significantly facilitated the release of PSTs from shellfish. The bioaccessibility of PSTs ranged from 80% to 95% in different shellfish. Cooking methods did not vary significantly in the dissolution of PSTs. It is recommended to cook shellfish by boiling to reduce exposure risk of PSTs. The transformation or degradation of PSTs occurred during the digestion process. Abstract: Current regulatory limit values for paralytic shellfish toxins (PSTs) in shellfish products are not considering the bioaccessibility of PSTs in seafood matrix during the gastrointestinal digestion for human beings. In this study, the bioaccessibility of PSTs in the shellfish cooked by different ways was assessed using a static in vitro human digestion model. Results showed that the dissolution of PSTs from shellfish tissues was not significantly affected by digestion time, ratios of solid weight to liquid volume (S/L) and cooking methods, but obviously facilitated by digestive enzymes. Different cooking ways reduced the contents of PSTs in shellfish by 45% to 88%, but did not significantly change the high bioaccessibility of PSTs that ranged from 80% to 95% in four different shellfish matrices. Transformation or degradation of PSTs occurred during the simulated digestion process. This work will help us to objectively assess the potential risks of PSTs to human health.